Respuesta :

Answer:

  g(x) = 3f(-x/2)

Step-by-step explanation:

g(x) is 3 times the height of f(x), and 2 times its width. It is also reflected over the y-axis.

The relevant transformations are ...

  g(x) = k·f(x) . . . . scales f(x) vertically by a factor of k

  g(x) = f(-x) . . . . . reflects f(x) over the y-axis

  g(x) = f(x/k) . . . . scales f(x) horizontally by a factor of k

__

The three transformations we described at the beginning mean that g(x) is ...

  g(x) = 3f(-x/2)

Ver imagen sqdancefan
ACCESS MORE